Predicting the distribution of potentially suitable habitat in China for Cirsium japonicum Fisch. ex DC. under future climate scenarios based on the R‐optimized MaxEnt model - Hu‐Qiang Fang; Zi‐Xuan Jiang; Shi‐Mao Chen; Tao Xie; Yu Xue; Jia Song; Qing‐Shan Yang (Ecology and Evolution, 2024)
Abstract Cirsium japonicum contains a variety of medicinal components with good clinical efficacy. With the rapid changes in global climate, it is increasingly important to study the distribution of species habitats and the factors influencing their adaptability. Utilizing the MaxEnt model, we forecasted the present and future distribution regions of suitable habitats for C. japonicum under various climate scenarios. The outcome showed that under the current climate, the total suitable area of C. japonicum is 2,303,624 km2 and the highly suitable area is 79,117 km2. The distribution of C. japonicum is significantly influenced by key environmental factors such as temperature annual range, precipitation of the driest month, and precipitation of the wettest month. In light of future climate change, the suitable habitat for C. japonicum is anticipated to progressively relocate toward the western and northern regions, leading to an expansion in the total suitable area. These findings offer valuable insights into the conservation, sustainable utilization, and standardized cultivation of wild C. japonicum resources.